Inclusion of detergent in a cleaning regime and effect on microbial load in livestock housing - Dodd, Christine E.R.; Hancox, L.R.; Le Bon, M.; Mellits, K.H. (BMJ Publishing Group, 2013)
Determining effective cleaning and disinfection regimes of livestock housing is vital to improving the health of resident animals and reducing zoonotic disease. A cleaning regime consisting of scraping, soaking with or without detergent (treatment and control), pressure washing, disinfection and natural drying was applied to multiple pig pens. After each cleaning stage, samples were taken from different materials and enumerated for total aerobic count (TAC) and Enterobacteriaceae (ENT). Soaking with detergent (Blast-Off, Biolink) caused significantly greater reductions of TAC and ENT on metal, and TAC on concrete, compared with control. Disinfection effect (Virkon S, DuPont) was not significantly associated with prior detergent treatment. Disinfection significantly reduced TAC and ENT on concrete and stock board but not on metal. Twenty-four hours after disinfection TAC and ENT on metal and stock board were significantly reduced, but no significant reductions occurred in the subsequent 96 hours. Counts on concrete did not significantly reduce during the entire drying period (120 hours). Detergent and disinfectant have varying bactericidal effects according to the surface and bacterial target; however, both can significantly reduce microbial numbers so should be used during cleaning, with a minimum drying period of 24 hours, to lower bacterial counts effectively.